Strategi Dinas Tenaga Kerja Kabupaten Sidoarjo dalam Mengembangkan Kompetensi dan Produktivitas Tenaga Kerja di Kabupaten Sidoarjo - Febiyanti Tri Setyo Astuti; Riana Puspa Dewi Santoso; Hafizh Akbar Dwi Krisna; Fasya Angga Febriwan; Sri Wibawani (VISA: Journal of Vision and Ideas, 2024)
This article reviews the strategies carried out by the Sidoarjo Regency Manpower Office in realizing the organization's vision and mission, namely, developing workforce competence and productivity in Sidoarjo Regency. This research aims to determine the implementation of competency and productivity development through 3 programs, namely job training, job matching and job fair in Sidoarjo Regency. In this study, this study is a type of qualitative research with a descriptive analysis method. The techniques used to collect primary and secondary data in this study are observation, interviews, documentation and library research. The primary data source of this study is the results of interviews with officers in the Sidoarjo Regency Manpower Office in the field of work training and labor productivity as well as the field of workforce planning and placement. So that the results of competency and productivity development are obtained through 3 programs, namely job training that is provided free of charge in every sub-district in Sidoarjo Regency, job matching is a special job fair program for vocational schools in Sidoarjo Regency, and job fair is a job fair that can be attended by the entire workforce that is not hindered from increasing work productivity, providing career opportunities, or finding potential employees. In addition, the existence of this program has an influence on the open unemployment rate in Sidoarjo Regency which can decrease every year.